William Dunbar : Scientific Pioneer of the Old Southwest - DeRosier, Arthur H. (Book collections on Project MUSE., 2007)
In 1804, while Lewis and Clark were still making their way up the Missouri River, Thomas Jefferson formulated a plan for a similarly ambitious exploration that would proceed from the Mississippi up the Red River ""to the tops of the mountains"" and then return by way of the Arkansas River. The man he selected to lead this venture was William Dunbar (1750--1810) of the Mississippi Territory. The Scottish-born Dunbar was a man of many abilities and professions -- surveyor, botanist, zoologist, astronomer, planter, architect, inventor. He perfected the cotton bale, learned how to put cottonseed o